Neuro-fuzzy modeling for multi-objective test suite optimization - Anwar, Zeeshan; Ahsan, Ali; Çatal, Çağatay (Walter De Gruyter Gmbh, Genthiner Strasse 13, D-10785 Berlin, Germany, 2016)
Regression testing is a type of testing activity, which ensures that source code changes do not affect the unmodified portions of the software adversely. This testing activity may be very expensive in, some cases, due to the required time to execute the test suite. In order to execute the regression tests in a cost-effective manner, the optimization of regression test suite is crucial. This optimization can be achieved by applying test suite reduction (TSR), regression test selection (RTS), or test case prioritization (TCP) techniques. In this paper, we designed and implemented an expert system for TSR problem by using neuro-fuzzy modeling-based approaches known as "adaptive neuro-fuzzy inference system with grid partitioning" (ANFIS-GP) and "adaptive neuro-fuzzy inference system with subtractive clustering" (ANFIS-SC). Two case studies were performed to validate the model and fuzzy logic, multi-objective genetic algorithms (MOGAs), non-dominated sorting genetic algorithm (NSGA-II) and multi-objective particle swarm optimization (MOPSO) algorithms were used for benchmarking. The performance of the models were evaluated in terms of reduction of test suite size, reduction in fault detection rate, reduction in test suite execution time, and reduction in requirement coverage. The experimental results showed that our ANFIS-based optimization system is very effective to optimize the regression test suite and provides better performance than the other approaches evaluated in this study. Size and execution time of the test suite is reduced up to 50%, whereas loss in fault detection rate is between 0% and 25%.
Keywords: Regression testing; test suite optimization; neuro-fuzzy modeling; computational intelligence; Test-Case Prioritization; Inference System; Algorithms; Anfis